Birth order and social outcomes, England, 1680-2024 - Gregory Clark; Neil Cummins (European Historical Economics Society (EHES), 2024)
Children early in the birth order get more parental care than later children. Does this significantly affect their life chances? An extensive genealogy of 428,280 English people 1680-2024, with substantial sets of complete families, suggests that birth order had little effect on social outcomes either for contemporary outcomes, or in earlier centuries. For a small group of elite families in the nineteenth century and earlier, the oldest son was advantaged in terms of wealth, education, and occupational status. But even in this elite group, among later sons, birth order had no effect. We consider in the paper how the absence of birth order effects in England can be reconciled with reports of substantial negative birth order effects for modern Nordic countries.
Keywords: J24; J62; N33; N34; 330; Human Capital Formation; Birth Order; Intergenerational Mobility